Global Universal Basic Skills: Current Deficits and Implications for World Development - Sarah Gust; Eric A. Hanushek; Ludger Woessmann (Institute of Labor Economics (IZA), 2022)
How far is the world away from ensuring that every child obtains the basic skills needed to be internationally competitive? And what would accomplishing this mean for world development? Based on the micro data of international and regional achievement tests, we map achievement onto a common (PISA) scale. We then estimate the share of children not achieving basic skills for 159 countries that cover 98.1% of world population and 99.4% of world GDP. We find that at least two-thirds of the world's youth do not reach basic skill levels, ranging from 24% in North America to 89% in South Asia and 94% in Sub-Saharan Africa. Our economic analysis suggests that the present value of lost world economic output due to missing the goal of global universal basic skills amounts to over 700 trillion over the remaining century, or 11% of discounted GDP.
Keywords: I25; O15; O47; 330; skills; student achievement; development goals; economic growth